The Muslim brotherhood [ Hasan al-Hudaybi and ideology - Zollner, Barbara H. E. , 1968- (Routledge studies in political Islam, 2009)
The Muslim Brotherhood is one of the influential Islamist organisations. This book provides an analysis of the Muslim Brotherhood during the years of al-Hudaybi's leadership, and how he sought to steer the organization away from the radical wing, inspired by Sayyid Qutb, into the more moderate Islamist organization